Rare earth element-doped porous In2O3 nanosheets for enhanced gas-sensing performance - Zhang, Wen-Hui; Ding, Su-Jun; Zhang, Qing-Song; Yi, Hui; Liu, Zi-Xiang; Shi, Meng-Li; Guan, Rong-Feng; Yue, Lu (Rare metals, 2021)
Rare earth (La, Pr, Sm, Ce and Yb)-doped porous In 2 O 3 nanosheets are prepared by a solvothermal method. The effect of rare earth elements on the structure, morphologies and gas-sensing performance of In 2 O 3 nanosheets is systematically investigated. The mixed phase composed of c-In 2 O 3 and rh-In 2 O 3 can be transformed into rh-In 2 O 3 by doping with rare earth elements. After doping with rare earth elements, the morphology can be changed from compact nanosheets to porous sheets. Compared with pure In 2 O 3 and La, Pr, Sm, Ce-doped porous In 2 O 3 nanosheets, Yb-doped In 2 O 3 nanosheets present the best gas-sensing performance. Among 3%–10% Yb-doped samples, 6% Yb-doped In 2 O 3 porous nanosheets exhibit the optimal gas-sensing performance to 5 × 10 −6 –750 × 10 −6 acetone, giving a high response of 15.3 toward 50 × 10 −6 acetone and fast response/recovery time at the operating temperature of 220 °C. Moreover, 6% Yb-doped porous In 2 O 3 nanosheet sensor also exhibits excellent selectivity and stability, indicating its potential in the next-generation gas sensor. Graphic abstract